Discharging Medically Complex Infants with Supplemental Nasogastric Tube Feeds: Impact on Neonatal Intensive Care Unit Length of Stay and Prevention of Gastrostomy Tubes - Mago-Shah, Deesha D.; Malcolm, William F.; Greenberg, Rachel G.; Goldstein, Ricki F. (American Journal of Perinatology, 2020)
Objective The aim of this study is to evaluate the feasibility, safety, and efficacy of discharge with supplemental nasogastric tube (NGT) feeds in medically complex infants.Study Design Cohort study of 400 infants enrolled in the Transitional Medical Home (TMH) program at Duke University Level IV neonatal intensive care unit from January 2013 to 2017.Results Among 400 infants enrolled in the TMH, 57 infants were discharged with an NGT. A total of 45 infants with a variety of diagnoses and comorbidities were included in final analysis. Among 45 infants, 5 obtained a gastrostomy tube (GT) postdischarge. Median (25–75th percentile) length of use of NGT in 40 infants was 12 days (4–37). Excluding four outliers who used NGT for ≥140 days, the median length of use was 8 days (3–24). This extrapolates to a median of 288 hospital days saved for the remaining 36 infants. There were only three emergency room visits related to parental concern for incorrect NGT placement. There was no statistically significant difference in percent oral feeding predischarge or growth in first month postdischarge between infants who orally fed versus those who obtained GTs.Conclusion Discharge with supplemental NGT feeds is safe and feasible utilizing a standardized protocol and close postdischarge follow-up. This practice can decrease length of stay and prevent need for GT.Key Points
Keywords: infant; newborn; premature; feeding problem; nasogastric tube; gastrostomy tube; medical home